Phonetics in English language teaching - Carley, Paul (Linguist) (Logos studies in language and linguistics, 2016)
After a period during which pronunciation teaching has been somewhat out of favour in English Language Teaching (ELT), interest has revived in recent years. It is important, therefore, that sources are made available for applied linguists better to understand past approaches to pronunciation teaching. This new six-volume collection, co-published by Routledge and Editions Synapse, assembles all the key material in a one-stop reference resource. The collection gathers includes seminal texts by Harold Palmer, A. Lloyd James, and C. K. Ogden, and major works by Edmund Tilley, H. A. Harman, and J. D. O'Connor